INFLUENCE OF RISK FACTORS ON THE DEVELOPMENT OF PREMATURE SEPARATION OF A NORMALLY LOCATED PLACENTA - Shodieva , Kh.T.; Rakhmatova , E.N.; Tolipova , Kh.T. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
This paper presents a review of the literature on the study of various aspects of premature detachment of a normally located placenta (PDNLP), which is considered one of the most severe complications of pregnancy and childbirth. This pathology is one of the current problems in obstetrics, it occurs acutely, is accompanied by bleeding of varying intensity, which is the cause of maternal and perinatal complications. Therefore, conducting any research work on the study of various aspects of this complication and, especially, on the prevention and elimination of risk factors for the occurrence of PDNLP, has medical and social significance.